An Analysis of the Implementation of Khot Learning at Nahdlatul 'Ulum Islamic Boarding School - Nahdla, Naila Cahya; Syaifullah, Muhammad; Amalia, Dian Risky (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The Lack of attention to the writing aspect in khot learning can have a negative impact on students' ability to understand and interpret the rules of khot. This study aims to analyze the implementation of khot learning at the Nahdlatul 'Ulum Metro Lampung Islamic Boarding School and identify the obstacle factors. The approach of this research uses qualitative descriptive methods and data collection in this study is by observation, interview, and documentation techniques. The data analysis used in this study is a miles and huberman analysis through data reduction, data presentation, and conclusions. The result of this research is that Khot Learning is carried out in a structured manner through four stages: The introduction stage as the initial basic understanding, the basic practice stage as strengthening, the development stage as the deepening stage, and the application and creativity stage as the stage of art production and expression. And obstacles in learning khot are technical obstacles such as inadequate infrastructure and limited time, non-technical obstacles such as the motivation and interests of students who are not the same, as well as academic/pedagogical obstacles such as difficulties in asking questions and difficulties in understanding the structure, arrangement, and writing techniques of Arabic letters.